Estudio geológico para el análisis de la susceptibilidad del terreno, en la comunidad las Lagunas cantón Saraguro provincia de Loja. - Morocho Piedra, Diego Esteban (2015)
The present thesis work carries out the geological survey for the analysis and the determination of zones susceptible to landslides in the Las Lagunas community, Saraguro canton province of Loja, for which purpose has been carried out the analysis by following the Heuristic method for the variables of the sector in study by giving more emphasis to the geological conditions being of greater complexity the parameter related to the geotechnical properties of the materials. For the development of this paper, there was performed a series of proposed activities in obtaining the field data like cabinet, among which there can be indicated the topographical survey, geological, geomorphological, land use, in addition to the application of indirect prospecting techniques in this instance SEV (vertical electrical sounding), and direct canvassing such as Standard Penetration Test (SPT) which enabled geotechnical characterization of the geo materials. In the final outcome of susceptibility four very important factors were taken into account such as geology, geomorphology, use of land and slopes all of the variables mentioned above were designed for representing each one of the thematic mapping thanks to the Geographical Information Systems (ArcGIS 10.1) which moreover allows superimposing maps with functional tools as the weighted summation in which as a result it is obtained the landslide susceptibility map categorized into five categories ranging from very low to the 17.94% Low 33% Medium 13.01% High 11.80% and very high with 11.64% of the total study area. The outcome of this investigation will be very useful for the inhabitants and leaders of the community at urban development projects or other private constructions which have been scheduled for the future.